The influence of psychological capital in the hotel industry following the COVID-19 pandemic - Iskandar, Vido; Kartika, Endo Wijaya; Kristianto, David (Bahasa Indonesia, 2024)
Covid-19 pandemic has impacted tourism sector terribly due to travel restrictions. Various methods have been implemented by the government to reinstate the confidence of society towards tourism destinations’ safety. East Java is one of the provinces becoming the government’s main focus for tourism recovery, and when people finally return, accommodation service is becoming necessity. Hotel’s management and staff need to perform numbers of adjustments to regain its visitors’ confidence and convenience upon using provided products and services. Hotel’s employees are expected to provide excellent service and performance. Thus, every member of the property is expected to possess positive psychological condition in order to be able to process and proceed with necessary operational changes on the place. This positive psychological state is often called as psychological capital (psycap). Employees with a higher psycap should have a higher readiness for change, which leads to a better job performance. Data collection through online questionnaires survey, with purposive sampling from 385 respondents. Quantitative data analysis using Partial Least Square (PLS) SEM. The findings show that psycap has a positive and significant impact on both readiness for change and job performance. Additionally, readiness for change positively and significantly influences job performance and serves as a mediating variable between psycap and job performance. This research aids management in understanding the connection between psycap, readiness for change, and job performance, particularly in the hotel industry.